The effectiveness of online recruitment / Nurul Huda Ghazali - Ghazali, Nurul Huda (2013)
The research objective is to understand the effectiveness using an online recruitment system at Pusat Kerjaya Amanjaya, UTC Kinta, Perak. To narrow down the scope, I was decided to choose employees and employer that worked in private sector at Pusat Kerjaya Amanjaya. Besides, I am going to study the whether the size of organization gives an effect to the usage of online recruitment, how the flow of communication going well when using online recruitment and the attraction of web design and its contents when user use online recruitment.